Red cell indices and peripheral blood film findings of anti-Psychotic treatment and treatment naïve Psychiatic patients in a tertiary Hospital in Nigeria. (Bangladesh Journal of Medical Science, 2019)
Background: The overall burden of morbidity and mortality from psychiatric disorders is on the rise. Holistic approach in the care of this group of patients has become inevitable. There is need for collaboration between psychiatrists and other physicians, laboratory physicians inclusive. Study design: cross sectional descriptive case- control study.Materials and method: A total of 198 patients including controls were recruited for this study. Patients with schizophrenia constituted majority of the respondents, 86.4% of antipsychotic-naïve patients and 90.9% of patients on antipsychotics. A comprehensive medical examination was carried out on every participant. On every sample, automated Full Blood Count was performed using Sysmex2000i and peripheral blood film was made and examined.Result: 51.5% and 47% of anti-psychotropicnaïve patients and patients on anti-psychotic were 18-40 and 41-60 years respectively. Male (57.6%), predominated the anti-psychotic naïve group while female (51.5%) predominated the group on anti-psychotics. Schizophrenia was the diagnosis in the majority of patients, 86.4% and 91% respectively in anti-psychotic naïve and antipsychotic treatment groups. Other diagnoses were depressive illness, substance use disorder and dementia. Of all the subjects, one (1.5%) schizophrenic patients and two (3%) of controls had abnormal haemogram results. For the schizophrenic patient with abnormal results, haematocrit was 12g/dl, MCV of 75fl and MCH of 26pg, while the two controls with abnormal results had only haematocrit deranged with value of 12.3g/d. Neutrophil hypersegmentation was seen on the film of five antipsychotic-naïve patients (7.5%) diagnosed with Schizophrenia and one (1.5%) of the controls. Macrocytosis was only seen in three (4.5%) of the five antipsychotic-naïve patients that had neutrophil hypersegmentation.Conclusion: No significant difference was noted in the Full Blood Counts among the two sets of patients and controls, although there were isolated cases of neutrohil hyperesegmentation and macrocytosis.Bangladesh Journal of Medical Science Vol.18(2) 2019 p.196-205